2011
DOI: 10.1159/000323343
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Large Animal Model for Investigation of Deep Brain Stimulation for Epilepsy

Abstract: Background/Objectives: To better understand the mechanism of action of deep brain stimulation (DBS) for epilepsy and to investigate implantable device features, it is desirable to have a large animal model to evaluate clinical-grade systems. This study assessed the suitability of an ovine model of epilepsy for this purpose. Methods: Animals were anesthetized for surgery and 1.5 T MRIs collected. Unilateral anterior thalamic DBS leads, hippocampal depth electrodes and catheters were implanted using a frameless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 75 publications
(42 reference statements)
7
39
0
1
Order By: Relevance
“…Figure 5 shows the morphology of the averaged EPs over the experimental period together with variation in the time‐to‐peak amplitude on consecutive days. Averaged EPs displayed a wave with latency of approximately 40 ms and amplitude of 0.02 mV, consistent with activation of the Circuit of Papez as seen in sheep models 22. Interestingly, there was a slight decrease in EP amplitude that occurred approximately 1 hour after each dose of levetiracetam once this was initiated (Fig 5).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Figure 5 shows the morphology of the averaged EPs over the experimental period together with variation in the time‐to‐peak amplitude on consecutive days. Averaged EPs displayed a wave with latency of approximately 40 ms and amplitude of 0.02 mV, consistent with activation of the Circuit of Papez as seen in sheep models 22. Interestingly, there was a slight decrease in EP amplitude that occurred approximately 1 hour after each dose of levetiracetam once this was initiated (Fig 5).…”
Section: Resultssupporting
confidence: 77%
“…In all cases, the dogs recovered without adverse neurologic effects and showed no outward sign of the effects of the implantation or stimulation. In addition, stimulation and recording from the electrodes showed that stimulation of the ANT can produce evoked responses identical to those obtained in other large animal models in which similar studies have been performed 22. The shape and latency of the EPs was consistent with activation of the circuit of Papez, suggesting that the dog is a suitable model for the testing of DBS strategies in the treatment of epilepsy.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This work was conducted in an ovine model recently developed in our laboratory to study DBS for epilepsy [18]. The prior study investigated stimulation and recording from nodes within the circuit of Papez, specifically the anterior nuclear (AN) region of the thalamus, and the hippocampus (HC).…”
Section: Introductionmentioning
confidence: 99%
“…(Adapted from [23] and [46]) amongst other approaches, DBS. For example, theta band activity within the septo-hippocampal circuit has been associated with decreased seizures [119,120], and continuous multimicroelectrode electrical stimulation using theta frequencies in a rat model of temporal lobe epilepsy decreases seizures (Desai et al, in preparation). Conceivably, the RNS could be adapted to accomplish this.…”
Section: Future Directionsmentioning
confidence: 99%